Advances in epidemiology and population-based prevention and control of cancers caused by asbestos exposure - Huang Qiulin; Lian Fuzhi; Chen Tianhui (生物医学转化)
Asbestos is a collective term for six natural mineral fibers that have been widely used commercially. These fibers are classified into two main groups: amphibole asbestos (including crocidolite, tremolite, actinolite, anthophyllite, and amosite) and serpentine fibers (primarily chrysotile), with chrysotile accounting for more than 90% of total asbestos production. According to the International Agency for Research on Cancer (IARC) Monographs on the Evaluation of Carcinogenic Risks to Humans, all types of asbestos are classified as Group Ⅰ carcinogens, with sufficient evidence of carcinogenicity in humans. Asbestos is a Group Ⅰ carcinogen for malignant mesothelioma, lung cancer, laryngeal cancer, and ovarian cancer. With the accelerating aging of the Chinese population and the cumulative effects of past asbestos exposure, the cancer burden attributable to asbestos exposure in China is expected to continue rising. This article systematically reviews the epidemiological data on asbestos-related cancers and population-based prevention and control strategies worldwide, aiming to provide scientific evidence for the prevention and control of asbestos-related cancers in China.